Study of microbiological purity with myramistin, anesthezine and CO2 extract of chamomile for use in surgical practice - L. L. Davtian; O. P. Shmatenko; V .A. Tarasenko; O. M. Vlasenko; G. V. Osedlo; N. М. Orlova (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Any finished dosage forms, including soft dosage forms, are subject to microbial contamination. It can be caused by microbial contamination of plant-based medicinal raw materials, air, industrial premises, equipment, utensils, water, personnel's hands, general non-compliance with the sanitary and epidemic regime of production, etc. The aim of the study was to conduct a biological study of the developed cream with Miramistin, anesthesin and CO2 chamomile extract in terms of "microbiological purity" in accordance with the requirements of the State Pharmacopoeia of Ukraine. The object of the study was CO2 chamomile extract, anesthesin, miramistin, emulsifiers, the developed cream. Quantitative determination of the colony forming units of test microorganisms in suspensions was carried out by hanging in Petri dishes with soybean casein agar for bacteria and Saburo medium for fungi. Studies of the microbiological purity of the investigated samples of the cream were carried out in accordance with the requirements of the State Pharmacopoeia of Ukraine 1 ed., Paragraph 5.1.4.. Tests were performed using the direct sowing method. The assessment of the degree of microbial contamination of the investigated creams samples consisted of determining the total number of aerobic bacteria and fungi in 1.0 g of the sample, as well as the absence of bacteria of the family Enterobacteriaceae, St. aureus and Ps. aeruginosa. To verify the study conditions, a negative control study was performed using a sterile solvent for hanging on nutrient media. On the basis of experimental studies, it was found that the optimum method is membrane filtration for determining the total number of viable aerobic bacteria, and for fungi, the direct hanging method. In the course of the experiment, it was established that the total number of viable aerobic microorganisms is less than 100, and yeast and mold fungi are less than 10 per 1 g of each sample; St. aureus and Ps. aeruginosa and some other gram-negative bacteria are not defined, which meets the requirements of the State Pharmacopoeia of Ukraine.